STRATEGI PERENCANAAN PENGEMBANGAN DESA WISATA PESISIR “PESONA BAHARI” GISIK CEMANDI - Eka Dian Savitri; Hermanto Hermanto; Ratna Rintaningrum; Saifulloh Saifulloh; Dyah Satya Yoga (ABDIMAS, 2022)
To ensure that the concept of service is in accordance with the community's needs, community service activities should begin with a needs assessment and a well-thought-out strategy. The goal of this research is to present an analysis and strategy for the development of the "Pesona Bahari" tourism hamlet in Gisik Cemandi. Data is gathered through observation and discussed. The data will also be submitted to a SWOT analysis. Based on the results of the SWOT analysis and observations of several available tourism objects, the initial mentoring strategy is carried out in three stages (period 2021-2022), namely (1) developing tourism concepts and guiding practices based on tourism, (2) promoting the branding of processed fish products as tourist village souvenirs, and (3) developing social media content and websites as a form of tourist village promotion. Meanwhile, because they must negotiate with the triple helix (government, private sector, and educational institutions), the creation of tourist village facilities will not be completed until the next year. Mentoring activities are carried out using andragogy principles, such as utilising participants' experiences to solve problems and forming working groups to ensure that tourism village development activities are self-sufficient and long-term.